1983
DOI: 10.1177/000456328302000603
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and Biochemical Parameters in an Industrial Workforce

Abstract: Biochemical and haematological data for two consecutive years are presented on about 2000 people from the workforce of a large chemical company. The data are examined for the influence of sex, age, season, time of blood sampling, and patterns of work on the various indices. In addition to the results confirming previously published work relating to the effects of age and sex, they provide interesting new information on the possible influences of seasons and patterns of work, that is, whether the subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…1 The present work on men confirms the influence of age but also introduces and attempts to quantify seasonal variations which we have observed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…1 The present work on men confirms the influence of age but also introduces and attempts to quantify seasonal variations which we have observed.…”
Section: Discussionsupporting
confidence: 73%
“…1 As part of an annual medical examination offered to each member of the workforce, blood samples were taken for haematological and biochemical analysis for five consecutive years, 1979-83. When undertaking the screening of our workforce the aims were to provide early evidence of target organ damage following exposure to substances known to be potentially toxic and to monitor workers being exposed to new substances for early evidence of any toxic effects.…”
mentioning
confidence: 99%
“…Nonetheless, no circannual rhythm in morning values of total leukocytes or lymphocytes has been found by others (7,19). In a recent study, large seasonal variations in morning total leukocyte count were found in young men, but not in men older than 40 yr (37). A reproducible circannual rhythm in the count of circulating B lymphocytes was documented in a healthy young Japanese subject sampled monthly between 9:00 and 1 1:00 h for 2 consecutive yr, with a peak in August (summer) and a nadir in January (winter) (5).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have observed significant seasonal differences in total number of peripheral blood leucocytes with peaks occurring in winter and troughs in summer (Reinberg et al 1980;Gidlow et al 1983;Reinberg & Smolensky, 1983). These findings are in contrast with results from the present study which observed reductions in circulating levels of lymphocyte subsets in winter.…”
Section: Baselinementioning
confidence: 99%